2008
DOI: 10.1007/s10840-008-9283-5
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of incessant orthodromic reciprocating tachycardia in a child with congenitally corrected transposition of great arteries and ebsteinoid malformation of left atrioventricular valve

Abstract: We report about a patient with congenitally corrected transposition of the great arteries and ebsteinoid malformation of left atrioventricular (AV) valve who presented with incessant orthodromic atrioventricular reciprocating tachycardia due to a left posteroseptal accessory pathway. Radiofrequency catheter ablation using trans-septal approach successfully eliminated the posteroseptal pathway across the morphologic tricuspid valve. This report highlights the importance of delineating the anatomy of the interat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…All the APs in patients with AV discordance were located around the anatomical TV, in close proximity to the posterior to lateral side of the valve. This finding is consistent with that of previous reports . Two patients had Ebstein‐like TV in this study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…All the APs in patients with AV discordance were located around the anatomical TV, in close proximity to the posterior to lateral side of the valve. This finding is consistent with that of previous reports . Two patients had Ebstein‐like TV in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Catheter ablation (CA) for supraventricular tachycardia (SVT), including atrioventricular reciprocating tachycardia (AVRT) caused by an accessory pathway (AP) in high‐risk groups such as those with a past history of SVT, is important because SVT may cause a collapse of hemodynamics in patients with complex congenital heart disease . Some case reports mentioned the usefulness of CA for AVRT in AV discordance; however, little is known about the effectiveness and impact of CA in patients with AV discordance in differing clinical scenarios such as those in our 11 cases. Some studies reported a high prevalence of TV anomalies in AV discordance, and some patients had Ebstein‐like/Ebsteinoid TVs .…”
Section: Introductionmentioning
confidence: 99%
“…In our clinic, ablation is performed using transseptal puncture for all left-sided APs in pediatric patients. Although transseptal puncture in patients with congenital heart diseases is difficult, it can be successfully performed by tagging of the septum ( 2 , 8 ).…”
Section: Discussionmentioning
confidence: 99%